Investigation of PALB2 Mutation and Correlation With Immunotherapy Biomarker in Chinese Non-Small Cell Lung Cancer Patients - Zhang, Jiexia; Tang, Shuangfeng; Zhang, Chunning; Li, Mingyao; Zheng, Yating; Hu, Xue; Huang, Mengli; Cheng, Xiangyang (Frontiers in Oncology, 2022)
Background PALB2, a gene in the homologous recombination repair (HRR) pathway of the DNA damage response (DDR), is associated with the efficacy of platinum-based chemotherapy, immunotherapy, and PARP inhibitor therapy in several tumors. However, the PALB2 characteristics, its correlation with immunotherapy biomarker, and the prognostic effect of immunotherapy in non-small cell lung cancer (NSCLC) were unknown. Methods Tumor tissue samples from advanced Chinese NSCLC patients were analyzed by next-generation sequencing (NGS) (panel on 381/733-gene). Tumor mutation burden (TMB) is defined as the total number of somatic non-synonymous mutations in the coding region. Microsatellite instability (MSI) was evaluated by NGS of 500 known MSI loci. Programmed Cell Death-Ligand 1 (PD-L1) expression was evaluated using immunohistochemistry (Dako 22C3 or SP263). One independent cohort (Rizvi2018.NSCLC.240.NGS cohort) containing genomic and clinical data from 240 patients with advanced NSCLC and two cohorts (the OAK and POPLAR study cohort) containing genomic and clinical data from 429 patients with advanced NSCLC were used to analyze the prognostic effect of PALB2 on immunotherapy. Results Genetic mutation of 5,227 NSCLC patients were analyzed using NGS, of which 162 (3.1%) harbored germline PALB2 mutation (PALB2gmut) and 87 (1.66%) harbored somatic PALB2 mutation (PALB2smut). In NSCLC patients with PALB2gmut and PALB2smut, the most frequently mutated gene was TP53 (65%, 64%). PALB2smut (14.52 Muts/Mb) was associated with higher TMB (p < 0.001) than PALB wild-type (PALB2wt) (6.15 Muts/Mb). However, there was no significant difference in TMB between PALB2gmut (6.45 Muts/Mb) and PALB2wt (6.15 Muts/Mb) (p = 0.64). There was no difference in PD-L1 expression among PALB2gmut, PALB2smut, and PALB2wt. In the Rizvi2018.NSCLC.240.NGS cohort, there was no difference in progression-free survival (PFS) (HR =1.06, p = 0.93) between PALB2 mutation (3.15 months) and PALB2wt (3.17 months). The OAK and POPLAR study cohort of NSCLC patients showed that there was no difference in overall survival (OS) (HR =1.1, p = 0.75) between PALB2 mutation (10.38 months) and PALB2wt (11.07 months). Conclusions These findings suggest that PALB2 may not be used as a biomarker for determining prognosis on immunotherapy in NSCLC.